Design and Docking Studies of Peptide Inhibitors as Potential Antiviral Drugs for Dengue Virus Ns2b/Ns3 Protease - Velmurugan, Devadasan; Mythily, Udhayakumar; Rao, Kutumba (Protein and Peptide Letters, 2014)
Dengue virus (DENV), one of the members of genus Flavivirus is emerging as a global threat to human health. It had led to the emergence of dengue fever (flu-like illness), dengue shock syndrome, and the most severe dengue hemorrhagic fever (severe dengue with bleeding abnormalities). As Dengue hemorrhage diseases are the life-threatening ones, attempts are being made worldwide to design inhibitors for DENV-2 NS2B-NS3 protease. NS2B/NS3 protease plays a vital role in the replication of dengue virus. The trypsin-like serine protease domain of NS3 contains the functional catalytic triad His-51, Asp-75, and Ser-135 in the N-terminal region. Inhibition of the NS3 protease activity is expected to prevent the propagation of dengue virus. Current drug discovery methods are largely inefficient and thus relatively ineffective in tackling the growing threat to public health presented by emerging and remerging viral pathogens. Recently, there has been a need of interest in peptides and their mimetics as potential antagonists for dengue protease because these small peptides are unlikely to invoke an immune response since they fall below the immunogenic threshold. They are often potent and display fewer toxicity issues than small-molecule compounds as a result of high specificity. This study was conducted to design peptides as enzyme inhibitors of dengue virus NS3 protease through computational approach. Crystallographic structure of dengue protease was retrieved from Protein Data Bank (PDBID: 2FOM) and docked with the peptides and the results are analyzed. From the docking studies reported in this paper, tetrapeptide (Lys-Gly-Pro-Glu), pentapeptide (Ser-Ile-Lys-Phe-Ala) and hexapeptide (Ala-Ile-Lys-Lys-Phe-Ser) with glide energy -70.0 kcal/mol, -72.2 kcal/mol and - 80.4 kcal/mol respectively show promising results which can be considered for further optimization and in vitro studies.
Keywords: peptide